Rancang Bangun Perangkat Lunak Sistem Pengiriman Paket Berbasis Website (Studi Kasus : PT. Sicepat Ekspres) - Enjel Melani Nubatonis; Farhan Haidar Rabbani; Irkham Shohibul Latif; Muhammad Fahmi Kashoif; Aries Saifudin (Jurnal Informatika Universitas Pamulang, 2022)
The design of a web-based package delivery system at PT Sicepat has used an automatic method. An application program used for sending packages at PT Sicepat has been in use for a old time, but there are still many problems with using application. Such as system maintenance when unwanted, some bugs or errors occur in the database. Managing package data collection is an important part of organizations and agencies working with other parties who have an interest. Which is carried out qualitatively, can provide an overview of the condition of the object of observation based on the available information. Data collection techniques used in direct interviews, data observation, data documentation, document analysis, and drawing conclusions are effective ways to collect information. System for receiving and sending packages. PT Sicepat Ekspres already has a desktop-based application-based computer system. A program will be proposed to support people sending packets through a web-based programming application. This application is expected to improve the delivery system which still does not meet the company's needs, by using the System Development Life Cycle (SDLC). The analysis and design method uses an object-oriented software engineering approach.